Numerical modeling of dielectric-resonator antennas in a complex environment using the method of moments. - Zhijun Liu (IEEE Transactions on antennas and propagation)
Aperture coupled dielectric resonator antennas (DRAs) that reside above a layered background are analyzed using the method of moments (MoM). Dyadic Green's functions for the layered medium are derived in a simple and effective manner and the Rao-Wilton-Glisson (RWG) function is used to expand both electric and magnetic currents. A transmission-line technique is used to compute the antenna-input impedance. Numerical results obtained for both hemispheric and rectangular DRAB agree well with published measurement results